The Effectiveness of using the AIR Learning Model (Auditory, Intellectually, and Repetition) in Improving Social Studies Learning Outcomes - Utami, Dinda Dwi; Saliman, Saliman; Widiastuti, Anik (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to evaluate the effectiveness of the AIR (Auditory, Intellectually Repetition) learning model in enhancing students' cognitive, psychomotor, and affective learning outcomes. The research employs an experimental approach using a pre-test and post-test design on selected student groups. Test results analyzed through the SPSS application indicate a significant improvement in learning outcomes before and after implementing the AIR model, with a significance value below 0.05. These findings suggest that the AIR model effectively enhances student learning. Additionally, an improvement in the psychomotor aspect was observed, as students demonstrated greater engagement when using the AIR model compared to traditional methods. Similarly, the affective aspect showed progress, as students exhibited responsibility in group settings by actively responding to teachers' questions. This reinforces the effectiveness of the AIR model in improving learning outcomes across cognitive, psychomotor, and affective domains. However, students with a kinesthetic learning style may not fully benefit from this approach, necessitating adjustments to accommodate their needs. This research is expected to contribute to the development of learning strategies that align with educational objectives across different levels